(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This research paper explores the pivotal role of the Mahisagar District Legal Services Authority in promoting Alternative Dispute Resolution (ADR) mechanisms. It examines the effectiveness of ADR in resolving disputes, the challenges faced, and the impact on the local community. The study highlights the importance of legal aid and the integration of ADR in the judicial process to enhance access to justice.